Prokrastinasi Akademik Mahasiswa Pendidikan Matematika FKIP Universitas Nusa Cendana Kupang - Udil, Patrisius Afrisno (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2022)
This research aims to describe the academic procrastination of mathematics education students at FKIP Undana. It includes scores and categories of academic procrastination both generally and based on its indicators. The method used is descriptive quantitative. The population were all students of Mathematics Education Study Program FKIP Undana (N = 423) with sample of 266 students who were selected by simple random sampling. The instrument used is the Student Academic Procrastination Scale. The results showed that generally the academic procrastination of mathematics education students was identified in the moderate category with percentage of 47.37% and average score of 45.55. The percentage of students who experience academic procrastination in the high category is 19.17% and very high is 7.52%. The results also found that most of the students' academic procrastination was identified in the moderate category for 4 indicators, namely time management (37.59%), intention-action gap (41.73%), perceived-ability (60.53%), and social disturbance (50.00%). Furthermore, it is found that more than 20% students were identified to experience academic procrastination in high and very high category for the four indicators. On the indicator of emotional distress, most of the students had academic procrastination in the very high (5.26%), high (35.34%), and moderate (20.68%) category. Keywords: procrastination, academic procrastination, mathematics edication